5tea sense : milk tea / Nur Fatin Farzana Azman ...[et al.] - Azman, Nur Fatin Farzana (2022)
First of all, 5TEA SENSE is a business that is located at Ground Floor No.14, Jalan Austin Height 3/2, Taman Mount Austin, 81100 Johor Bahru, Johor. The name of the business come out from our idea together and the meaning behind 5TEA SENSE is 5TEA represent the number of employees that work together to open this business meanwhile Sense means taste and smell. This shows the way we picture our products and services so that our customers remember our business name so that we can expand our business. As for the business, we are providing bubble tea and desserts for residents that are living around Mount Austin. As we are comprehending the changes of environment, people these days don’t put on a very simple drinks and desserts on their daily meals. Therefore, we have to provide the citizens with a simple but tasty drinks and desserts that are high in product quality. The shop consist of five partner which is include general manager, administration manager, operation manager, marketing manager and financial manager. The market target for our business is from low to high income level. Moreover, business plan is necessary to all entrepreneur so that it is easy to prepare a group of people such as the owner itself, suppliers, customers and employees. We believe that we will able to reach the estimated business goal with the business financial position statement. There is also a guarantee of return modal within a short time and a current ratio will cover the liabilities and put the business in a comfort stage at its very highest of the company’s sale.